Platelet Hyporeactivity in Very Low Birth Weight Neonates - Rajasekhar, Damodara; Barnard, Marc R; Bednarek, Francis J; Michelson, Alan D (Thrombosis and Haemostasis, 1997)
Very few studies have examined platelet function in very low birth weight (VLBW) preterm neonates, because of the relatively large volumes of blood required. In this study, platelet function in clinically stable VLBW neonates was examined by whole blood flow cytometry, which requires only 5 |jl1 of whole blood per assay. The following monoclonal antibodies were used: S12 (P-selectin-specific, reflecting a granule secretion), PAC1 (directed against the fibrinogen binding site exposed on the GPIIb-IIIa complex of activated platelets), F26 (directed against a conformational change in fibrinogen bound to the GPIIb-IIIa complex), and 6D1 (directed against the von Willebrand factor binding site on the GPIb-IX-V complex). VLBW neonates, like normal adults, did not have circulating activated platelets, as determined by the lack of binding of SI2, PAC1, and F26 in the absence of an added agonist. VLBW neonatal platelets were markedly less reactive than adult platelets to thrombin, ADP/epinephrine, and U46619 (a stable thromboxane A2 analogue), as determined by the extent of increase in the platelet binding of SI2, PAC1, and F26, and the extent of decrease in the platelet binding of 6D1. In summary, compared to adults, the platelets of VLBW neonates are markedly hyporeactive to thrombin, ADP/epinephrine and a thromboxane A2 analogue in the physiologic milieu of whole blood, as determined by: 1) the increase in platelet surface P-selectin; 2) the exposure of the fibrinogen binding site on the GPIIb-IIIa complex; 3) fibrinogen binding; and 4) the decrease in platelet surface GPIb. This platelet hyporeactivity may be a factor in the propensity of VLBW neonates to intraventricular hemorrhage. In addition to its previously defined use as a test of platelet hyperreactivity, the present study suggests that whole blood flow cytometry may be useful in the clinical assessment of platelet hyporeactivity.